A new approach to the analysis of heat and mass transfer characteristics for laminar air flow inside vertical plate channels with falling water film evaporation. (December 2016) - Ren, Chengqin; Wan, Yangda
Highlights: A new approach is proposed to calculate average Nusselt and Sherwood numbers. A similarity analysis is performed to find out the dimensionless parameters. The effects of the various dimensionless parameters are studied in detail. Abstract: The purpose of this study is to develop a new method for analyzing the combined heat and mass transfer characteristics in laminar moist air flow inside vertical plate channels with falling water film evaporation. A two-dimensional computational fluid dynamics (2-D CFD) model is firstly utilized to simulate the laminar convection heat and mass transfer processes. Further, a one-dimensional (1-D) model is utilized to analyze the average Nusselt and Sherwood numbers based on the numerical results of the 2-D model. Thus, the 1-D model can be utilized to retrieve the 2-D model results. Furthermore, a similarity analysis is performed to reduce the original 2-D model equations into dimensionless forms so as to find out the minimum set of grouped dimensionless factors affecting the average Nusselt and Sherwood numbers. Finally, the effects of moist air inlet Reynolds number Re g, the ratio of water to moist air mass flow rate R wg, the ratio of channel length to half channel width α L and moist air inlet dimensionless temperature θ g, i on the average Nusselt and Sherwood numbers are examined in detail. By the detailed examination, it is found that larger average Nusselt and Sherwood numbers result from conditions with higher R wg, Re g or θ g, i values or lower α L values but larger average Lewis factors result from conditions with higher R wg, α L or θ g, i values or lower Re g values.